2005
DOI: 10.1016/j.cardiores.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic immune response promotes the accumulation of host-derived smooth muscle cells in transplant arteriosclerosis

Abstract: Development of intimal thickenings during transplant vasculopathy involves an allogenic immune response, which promotes accumulation of host-derived SMCs and apoptosis of resident graft SMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
19
0
6
Order By: Relevance
“…Alloimmune activation is a prerequisite for the development of OAD. [13][14][15] This study supports the central role of IL-2-dependent T-cell-mediated alloimmune injury in the development of OAD. First, although mild inflammation is seen in syngeneic grafts due to graft ischemia during the first post-operative days, these grafts recover completely with normal histology 30 days after transplantation.…”
Section: Discussionsupporting
confidence: 78%
“…Alloimmune activation is a prerequisite for the development of OAD. [13][14][15] This study supports the central role of IL-2-dependent T-cell-mediated alloimmune injury in the development of OAD. First, although mild inflammation is seen in syngeneic grafts due to graft ischemia during the first post-operative days, these grafts recover completely with normal histology 30 days after transplantation.…”
Section: Discussionsupporting
confidence: 78%
“…Traditionally, it was believed that neointimal smooth muscle cells in transplant arteriosclerosis were derived from the excessive proliferation and migration of donor-derived medial smooth muscle cells [6,7] . Recently, several studies reported that the origin of neointimal smooth muscle cells were derived from recipient cells rather than the donor medial smooth muscle cells [8] . Our previous study suggested that recipient cells were the main source of neointimal cells [5] .…”
Section: Discussionmentioning
confidence: 99%
“…2,59 In analogy to wire injury-induced vascular remodeling, restraint of caspase 3-mediated apoptosis abates neointima formation in transplant arteriosclerosis. 60 Although direct evidence for apoptosis-induced SDF-1␣ expression in graft vasculopathy is lacking, SDF-1␣ is upregulated in the adventitia and subsequently in the media and neointima of aortic allografts and provokes mobilization and neointimal recruitment of SPCs.…”
Section: Vascular Remodeling By Sdf-1␣-mediated Recruitment Of Progenmentioning
confidence: 99%